Diagnosis and Treatment of Adrenal Medullary Hyperplasia: Experience from 12 Cases. (26th August 2014) - Yang, Lu; Gao, Liang; Lv, Xiao; Qian, Shengqiang; Bu, Siyuan; Wei, Qiang; Yuan, Jiuhong; Fan, Tianyong
Abstract : Objective . To dissect the characteristics of adrenal medullary hyperplasia (AMH) and share our experience of diagnosis and treatment of AMH. Methods . From 1999 to 2013, 12 cases of AMH have been pathologically diagnosed after operation in our hospital. The clinical characteristics, process of diagnosis, treatment, and prognosis during follow-up of all patients are summarized retrospectively. Results . Four cases were trended to be AMH and 6 cases were trended to be pheochromocytoma before operation; moreover, the other two patients were diagnosed accidentally. All patients, except for the patient with mucinous tubular and spindle cell carcinoma of left kidney by open surgery, experienced a smooth laparoscopic adrenalectomy, including 2 with radical nephrectomy, 10 of which experienced unilateral adrenalectomy, 1 was bilaterally partial adrenalectomy, and the remaining one was unilaterally complete removal and then 2/3 partially contralateral excision. After a medium follow-up of 6.5 years, it demonstrated a satisfactory outcome of 8 cured patients and 4 symptomatic improved patients. Conclusions . AMH presents a mimicking morphology and clinical manifestation with pheochromocytoma. Surgery could be the only effective choice for the treatment of AMH and showed a preferable prognosis after a quite long follow-up.